"Digital-first libraries" Developing and managing digital platforms and services in SMU Libraries - MOHAMMED ALI, Salihin (Institutional Knowledge at Singapore Management University, 2024)
Agenda: SMU Background Digital Transformation Areas Platform Management Trends & Challenges